In Arid Region... CIAH, Bikaner, serving resource poor farmers - Dutt, Som (Indian Horticulture, 2019)
On the occasion of Silver Jubilee celebration of ICAR-Central Institute for Arid Horticulture (CIAH), Bikaner (Rajasthan), the Editor (Indian Horticulture), ICAR-DKMA, New Delhi, interacted with Prof. (Dr) P.L. Saroj, Director of CIAH, Bikaner, on various R&D activities and farmers’ welfare centric programmes on arid and semi-arid horticulture. The excerpts of the interaction are furnished here.